Long term effects of public policy for displaced workers in Sweden - shipyard workers in the West and miners in the North - Henry Ohlsson; Donald Storrie (Uppsala University, Department of Economics, 2007)
The objective of this paper is to study the long term effects of public policy measures for displaced workers. Our focus is on the individuals affected by the cutbacks at the LKAB iron ore mines in northern Sweden in 1983 and the closure of the Uddevalla Shipyard in western Sweden in 1985. These workers not only experienced job loss, but were also the target group for extraordinary labour market policies. Using register data from Statistics Sweden (labour market status, earnings, education etc.), we follow those affected until 1999. We compare this with the corresponding development of a large sample other workers who lost their jobs because of plant closures in 198788 but who did not receive extraordinary measures. Estimations of the net effect of the extraordinary measures find that they did have positive long-term effects for the displaced shipyard workers and miners. They have higher employment, not higher unemployment, and higher earnings than the comparison group.
urn:nbn:se:uu:diva-210882
Keywords: J65; J68; L62; L72; 330; involuntary job loss; displacement; plant closures; cutbacks; labour market policy; employment; unemployment; earnings; Kündigung; Arbeitsmarktpolitik; Arbeitsvermittlung; Beschäftigung; Lohn; Vergleich; Schweden